An assessment of the agricultural tramline system project in the municipality of Atok, Benguet province - Manuel, Maria Amor C. (School of Urban and Regional Planning, University of the Philippines Diliman, 2016)
The study documented the experience of the users and non-users of the Agricultural Tramline System (ATS) in the Municipality of Atok in Benguet Province. The study sought to establish the benefits and challenges faced by the farmers in the study area, especially the transport of their produce to the market. Base on a purpose survey a profile of the ATS and non--ATS users was made. The profile covered the farmers, the farms and the transportation and marketing of the produce of ATS and non-ATS users. The study showed that there is a benefit in terms of cost savings for farmers using the ATS compared to the non-users. There is no difference between the transport time of ATS and non-ATS users but this is an improvement from the situation before when produce had to be hauled manually from the uplands before they can be brought to the market. The ATS has proven to be effective in providing accessibility from the uplands to the main roads in the study area. It should continue to be provided/constructed in areas that are physically inaccessible-only if these areas are production areas in need of access to the market. The ATS also poses less damage to the environment since there is no need to alter the natural physical condition of an area to be able to construct the ATS. For agricultural development planing, the ATS can be proposed as an intermediate mode of transport and alternative means of accessing hard-to-reach production areas, especially for those remote areas, which are not included in short-term plans for road construction.